Enhanced heat transfer by an original immersed spray cooling system integrated with an ejector. (1st September 2018) - Wang, Ji-Xiang; Li, Yun-Ze; Li, Jia-Xin; Li, Chao; Xiong, Kai; Ning, Xian-Wen
Abstract: Spray cooling is believed to be a promising candidate for the cooling of the next-generation high heat-flux electronics. Different from the traditional spray cooling (SC), a modified version of SC – immersed spray cooling (ISC) – is firstly proposed in this paper. Experimental set-up upon which thermal tests of SC, ISC and pool boiling can be conducted was established. In order to realize the multifunction of the experimental system, an ejector, which plays an important role to control the liquid level in the cooling chamber, is integrated in the experimental system. Based on the novel theory of suction according to the need, modelling, design, and fabrication of the ejector was conducted, which proves to be a success in the practical operation. We experimentally demonstrated that the ISC performs the best in terms of cooling performance in all the operating conditions. Comparative study between thermal performances between SC and ISC is the focus in this paper. A maximum 65.6% enhancement in heat flux was observed for the ISC when the surface temperature was 205.6 °C. The enhanced heat transfer of the ISC can be attained due to the vapor layer elimination and chaotic effect around the target surface. Highlights: An original immersed spray cooling (ISC) was proposed in this paper. An ejector-assisted fluid system was designed to control the liquid level. Modelling and fabrication of the ejector was conducted to ensure a durable run. Cooling performances of the ISC, SC and pool boiling were comparatively studied. A maximum heat flux enhancement was 65.6% for ISC compared with that of SC.